Spontaneous Hair Cell Regeneration Is Prevented by Increased Notch Signaling in Supporting Cells - McGovern, Melissa M.; Zhou, Luyi; Randle, Michelle R.; Cox, Brandon C. (Frontiers in Cellular Neuroscience, 2018)
During embryonic development, differentiation of cochlear progenitor cells into hair cells (HCs) or supporting cells (SCs) is partially controlled through Notch signaling. Many studies have shown that inhibition of Notch signaling allows SCs to convert into HCs in both normal and drug damaged neonatal mouse cochleae. This mechanism is also implicated during HC regeneration in non-mammalian vertebrates; however, the mechanism of spontaneous HC regeneration in the neonatal mouse cochlea is less understood. While inhibition of Notch signaling can force SCs to convert into HCs and increase the number of regenerated HCs, it is currently unknown whether this pathway is involved in spontaneous HC regeneration observed in vivo. Therefore, we investigated the role of Notch signaling during the spontaneous HC regeneration process using Atoh1-CreERTM::Rosa26loxP-stop-loxP-DTA/+ mice injected with tamoxifen at postnatal day (P) 0 and P1 to ablate HCs and stimulate spontaneous HC regeneration. Expression changes of genes in the Notch pathway were measured using immunostaining and in situ hybridization, with most changes observed in the apical one-third of the cochlea where the majority of HC regeneration occurs. Expression of the Notch target genes Hes1, Hes5, Hey1, HeyL, and Jagged1 were decreased. To investigate whether reduction of Notch signaling is involved in the spontaneous HC regeneration process, we overexpressed the Notch1 intracellular fragment (N1ICD) in cochlear SCs and other non-sensory epithelial cells in the context of HC damage. Specifically, Atoh1-CreERTM::Rosa26loxP-stop-loxP-DTA/+::Sox10rtTA::TetO-LacZ::TetO-N1ICD mice were injected with tamoxifen at P0/P1 to stimulate spontaneous HC regeneration and given doxycycline from P0-P7 to induce expression of N1ICD as well as LacZ for fate-mapping. We observed a 92% reduction in the number of fate-mapped regenerated HCs in mice with N1ICD overexpression compared to controls with HC damage but no manipulation of Notch signaling. Therefore, we conclude that increased Notch signaling prevents spontaneous HC regeneration from occurring in the neonatal mouse cochlea. Understanding which components of the Notch pathway regulates regenerative plasticity in the neonatal mouse cochlea will inform investigations focused on stimulating HC regeneration in mature cochlea and eventually in humans to treat hearing loss